2012
DOI: 10.3944/aott.2012.2632
|View full text |Cite
|
Sign up to set email alerts
|

The effect of medial side repair in terrible triad injury of the elbow

Abstract: Ulnar neuropathy is a common complication after medial collateral ligament injury and prophylactic release will facilitate overall results and postoperative patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 17 publications
0
31
1
6
Order By: Relevance
“…In the study reported by Toros et al [23], 6 of 16 (37.5%) patients experienced grade I arthrosis. In the study reported by Garrigues et al [22], 5 of 40 (12.5%) patients experienced heterotropic ossification.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…In the study reported by Toros et al [23], 6 of 16 (37.5%) patients experienced grade I arthrosis. In the study reported by Garrigues et al [22], 5 of 40 (12.5%) patients experienced heterotropic ossification.…”
Section: Resultsmentioning
confidence: 83%
“…The proportion of patients who required reoperation ranged from 0 to 54.5%, with most studies reporting that approximately 30% of patients experienced the need for reoperation. No patients required reoperation in 3 studies [15], [16], [23]. Overall, 70 of 312 (22.4%) patients experienced complications requiring reoperation.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…There are reports that in those patients who do not have an MCL repair, there are higher rates of ulnar nerve irritation and need for subsequent ulnar nerve surgery. 20,21 In acute injuries there may be a rupture of the flexorpronator muscle mass. Management depends on the level of instability.…”
Section: Repairmentioning
confidence: 99%